Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1128/jb.05450-11
|View full text |Cite
|
Sign up to set email alerts
|

FadD Is Required for Utilization of Endogenous Fatty Acids Released from Membrane Lipids

Abstract: FadD is an acyl coenzyme A (CoA) synthetase responsible for the activation of exogenous long-chain fatty acids (LCFA) into acyl-CoAs. Mutation of fadD in the symbiotic nitrogen-fixing bacterium Sinorhizobium meliloti promotes swarming motility and leads to defects in nodulation of alfalfa plants. In this study, we found that S. meliloti fadD mutants accumulated a mixture of free fatty acids during the stationary phase of growth. The composition of the free fatty acid pool and the results obtained after specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…The results obtained from the fadD deletion mutant, however, do not deny the existing LCFA transport mechanism that a LCFA molecule must be abstracted from the inner membrane by FadD to get into cytoplasm. The lipid composition in fadD deletion mutants is known to be different from the wildtype strain (Pech-Canul et al 2011), and there have not been any studies on whether the membrane structure is reasonably conserved when fadD is deleted. Therefore, experimental data with the fadD deletion mutant in this study cannot conclusively infer the detailed transport mechanism of the wild-type strain.…”
Section: Discussionmentioning
confidence: 98%
“…The results obtained from the fadD deletion mutant, however, do not deny the existing LCFA transport mechanism that a LCFA molecule must be abstracted from the inner membrane by FadD to get into cytoplasm. The lipid composition in fadD deletion mutants is known to be different from the wildtype strain (Pech-Canul et al 2011), and there have not been any studies on whether the membrane structure is reasonably conserved when fadD is deleted. Therefore, experimental data with the fadD deletion mutant in this study cannot conclusively infer the detailed transport mechanism of the wild-type strain.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it has been reported that members of the FadR regulon might be activated in stationary phase (20,67), and several fad genes have been reported to be upregulated during the stringent response (34). A recent report suggested that free fatty acids might accompany envelope remodeling during stationary phase (68), which might explain derepression of the fad genes. The reduced amount of FadR protein in stationary phase observed in our study, coupled with the increase in ppGpp concentration that occurs upon entry into stationary phase (63) and the resulting effects on FadR synthesis, might also contribute to effects on the FadR regulon (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli homolog FadL Ec is required for uptake of exogenous oleic and palmitic acids, but not for reutilization of membrane lipids (5,29). Thus, LCFA uptake through FadL likely is crucial only for utilization of exogenous fatty acids.…”
Section: Discussionmentioning
confidence: 99%